IDENTIFIKASI POTENSI LONGSORAN LERENG BERDASARKAN ANALISIS KINEMATIKA DI PT. HARMAK INDONESIA - Markus Ola; Singgih Saptono; Barlian Dwinagara (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2025)
Open-pit mining operations are strongly influenced by slope stability conditions throughout the mining process. Factors that influence slope stability including lithological distribution, slope geometry, surface conditions, and geological structures at both local and regional scales. This study aims to identify potential slope failures associated with the presence of discontinuity planes using a kinematic analysis approach. Geological structural data were collected using the scanline sampling method at three observation locations, yielding a total of 115 joint sets, and laboratory testing was conducted to determine the internal friction angle of the rock mass. Kinematic analysis was performed using Rocscience Dips software to evaluate the geometric relationships among discontinuity orientations, slope orientation, and the internal friction angle. The results indicate that at scanline 1 and scanline 2, potential wedge failures are classified as stable due to the absence of daylighting conditions, whereas at scanline 3, a potential planar failure was identified that kinematically satisfies all instability criteria. The presence of water and vibrations induced by excavation activities may act as triggering factors that reduce slope stability.